Histone acetyl transferases CBP and p300 are necessary for maintenance of renin cell identity and transformation of smooth muscle cells to the renin phenotype - Pentz, Ellen Steward (American Physiological Society, 2012)
In response to a homeostatic threat circulating renin increases by increasing the number of cells expressing renin by dedifferentiation and re-expression of renin in arteriolar smooth muscle cells (aSMCs) that descended from cells that expressed renin in early life. However, the mechanisms that govern the maintenance and reacquisition of the renin phenotype are not well understood. The cAMP pathway is important for renin synthesis and release: the transcriptional effects are mediated by binding of cAMP responsive element binding protein with its co-activators, CBP and p300, to the cAMP response element in the renin promoter. We have shown previously that mice with conditional deletion of CBP and p300 (cKO) in renin cells had severely reduced renin expression in adult life. In this study we investigated when the loss of renin-expressing cells in the cKO occurred and found that the loss of renin expression becomes evident after differentiation of the kidney is completed during postnatal life. To determine whether CBP/p300 is necessary for re-expression of renin we subjected cKO mice to low sodium diet + captopril to induce retransformation of aSMCs to the renin phenotype. The cKO mice did not increase circulating renin, their renin mRNA and protein expression were greatly diminished compared with controls, and only a few aSMCs re-expressed renin. These studies underline the crucial importance of the CREB/CBP/p300 complex for the ability of renin cells to retain their cellular memory and regain renin expression, a fundamental survival mechanism, in response to a threat to homeostasis.